Quantum dynamics in molecules and nanostructures in strong fields - Bubin, S. (Nazarbayev University, 2014)
With the advance of time-dependent probes the investigation of the dynamical behavior of matter at the nanoscale has become a very important research direction. Laser-assisted steering of the electron motion in molecules and manipulation of their structure and composition has been dreamt about since the very emergence of coherent light sources. Realizing new possibilities in selective photochemistry of complex molecular systems, however, requires good understanding of underlying quantum dynamics. First-principles quantum-mechanical simulations can be of great help in assisting experiments, understanding the complex quantum dynamics, and interpreting the experimental data.
Keywords: quantum; dynamics; photochemistry; molecular; electron; nanoscale; structure